Bowel injury complicating percutaneous cryoablation of large renal cell carcinoma - Miyazaki, Masaya (Radiol Case Rep, 2020)
We report the case of a bowel injury, which occurred after the percutaneous cryoablation (PCA) of large renal cell carcinoma (RCC). A 50-year-old man with RCC measuring 47 mm in diameter. First, we performed transarterial embolization for the tumor, followed by PCA with hydrodissection, which displaced the small intestine from the iceball. The procedure was completed without any complication on the procedural day; however, the patient complained of appetite loss and abdominal pain 2 days after PCA. Computed tomography revealed a bowel injury at the small intestine adjacent to the tumor. After 7 days, ileus tube insertion, and fasting, the patient recovered from the bowel injury and was discharged 10 days after PCA. He underwent a second PCA because of a small recurrent renal tumor 5 months after the first PCA without complications. This case indicated that a bowel injury after PCA for RCC could be treated conservatively.